Wpływ nadawcy na kształtowanie się relacji nadawczo-odbiorczych w blogu (na podstawie blogów tematycznych o literaturze kryminalnej) = Sender`s impact on the development of sender-receiver relations in a blog (based on thematic blogs about criminal literature) - Uździcka, Marzanna; Półtorak, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is an attempt to determine to what extent and in what way the autor of a blog, one of the most dynamically developing modern forms of communication in the Internet space, creates sender-receiver relations.
Keywords: blog; blog tematyczny; nadawca; odbiorca; komunikacja internetowa; thematic blog; sender; receiver; Internet communication